Menguak Mental Accounting pada Online Gamers (Studi pada Generasi Z) - Apriliana, Naomi (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study explores mental accounting among Generation Z online gamers, particularly Mobile Legends players, in Pontianak. It examines how players separate money spent on online games from money allocated for daily needs, savings, and other purposes, as well as how this separation influences their financial decisions and consumptive behavior. The study employs a qualitative approach using primary data collected through in-depth interviews with Generation Z players who had made in-game microtransactions. Interview data were coded and analyzed thematically. The findings show that players create separate mental accounts for daily necessities, savings, entertainment, and online gaming. Some players finance game-related spending through income earned from tournaments or gaming services and attempt to avoid using savings. However, these financial boundaries are not always consistently maintained. Funds initially allocated for savings or essential needs may be redirected to in-game purchases, particularly under emotional impulses, social pressure, or the desire for immediate gratification. Mental accounting therefore provides a budgeting structure but may also rationalize excessive spending and weaken financial self-control. The study concludes that improved financial awareness, expenditure monitoring, and budgeting discipline are required to prevent online gaming expenses from undermining personal financial stability.